2022
DOI: 10.3390/cancers14174138
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Early Onset Colorectal Cancer through Analysis of Normal Colon Organoids of Familial Adenomatous Polyposis Patients

Abstract: Early onset colorectal cancer (EOCRC) rates have increased in recent decades. While lowering the recommended age for routine colonoscopies to 45 may reduce this burden, such measures do not address those who develop CRC before that age. Additional measures are needed to identify individuals at-risk for CRC. To better define transcriptomic events that precede the development of CRC, we performed RNA-sequencing analysis in colon organoids derived from seven healthy and six familial adenomatous polyposis (FAP) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…This is significant as a dysregulated innate immune response has been found to be the main driver behind “inflammaging”, a phenomenon characterized by persistent low levels of systemic and tissue microenvironment inflammation 32 . Other studies investigating the relationship between certain environmental exposures and EOCRC‐related gene and metabolomic modifications have established links between inflammation, obesity, and the NOTCH1‐GATA4‐IRG1 axis, alcohol consumption and overexpression of NOTUM/GDF11, and red meat consumption and choline/tryptophan/bile acid accumulation and upregulation of phosphatidylcholine and tryptophan biosynthesis genes in EOCRC patients 33–35 . A Westernised diet has also been correlated with an EOCRC fecal taxa signature characterized by an abundance of Falvonifractor plautii, B. vulgatus, Alistipes putredinis, and Intestinomonas butyriciproducens species, resulting in decreased flavonoid degradation, increased proteolytic and elastase deficiency and thus inflammation 34,36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is significant as a dysregulated innate immune response has been found to be the main driver behind “inflammaging”, a phenomenon characterized by persistent low levels of systemic and tissue microenvironment inflammation 32 . Other studies investigating the relationship between certain environmental exposures and EOCRC‐related gene and metabolomic modifications have established links between inflammation, obesity, and the NOTCH1‐GATA4‐IRG1 axis, alcohol consumption and overexpression of NOTUM/GDF11, and red meat consumption and choline/tryptophan/bile acid accumulation and upregulation of phosphatidylcholine and tryptophan biosynthesis genes in EOCRC patients 33–35 . A Westernised diet has also been correlated with an EOCRC fecal taxa signature characterized by an abundance of Falvonifractor plautii, B. vulgatus, Alistipes putredinis, and Intestinomonas butyriciproducens species, resulting in decreased flavonoid degradation, increased proteolytic and elastase deficiency and thus inflammation 34,36 .…”
Section: Resultsmentioning
confidence: 99%
“…32 Other studies investigating the relationship between certain environmental exposures and EOCRCrelated gene and metabolomic modifications have established links between inflammation, obesity, and the NOTCH1-GATA4-IRG1 axis, alcohol consumption and overexpression of NOTUM/GDF11, and red meat consumption and choline/tryptophan/bile acid accumulation and upregulation of phosphatidylcholine and tryptophan biosynthesis genes in EOCRC patients. [33][34][35] A Westernised diet has also been correlated with an EOCRC fecal taxa signature characterized by an abundance of Falvonifractor plautii, B. vulgatus, Alistipes putredinis, and Intestinomonas butyriciproducens species, resulting in decreased flavonoid degradation, increased proteolytic and elastase deficiency and thus inflammation. 34,36 Although studies have demonstrated the correlation between numerous genes, inflammation and EOCRC, a reproducibly implicated gene remains to be identified and future research is needed.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…With the change of modern lifestyle, the incidence of colitis has gradually increased, and the prone population is very wide, difficult to cure, and the cancer rate is high, so it’s listed as one of the modern difficult diseases by the World Health Organization [ 91 ]. Long-term colitis and adenomatous polyposis can lead to contractions, perforations, and even bowel cancer [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ]. Colon cancer organoids can be derived based on iPSC technology [ 101 ].…”
Section: Construction Of Organoids Based On Ipsc Technologymentioning
confidence: 99%